The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1996
DOI: 10.1111/j.1524-4725.1996.tb00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Local Anesthetics

Abstract: Local anesthetics are safe and effective. With the understanding of the actions and interactions of this class of drugs, maximum patient safety and satisfaction can be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
15

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 60 publications
1
38
0
15
Order By: Relevance
“…7B) (370). The intermediate chain contains either an ester (tetracaine and procaine) or an amide (dibucaine and lidocaine) group.…”
Section: Talas and Related Compoundsmentioning
confidence: 99%
“…7B) (370). The intermediate chain contains either an ester (tetracaine and procaine) or an amide (dibucaine and lidocaine) group.…”
Section: Talas and Related Compoundsmentioning
confidence: 99%
“…A latência deve ser respeitada sob risco de provocar-se estímulo doloroso sem trazer benefício ao paciente. Alguns estudos mostraram que a mistura da solução de anestésico local com bicarbonato de sódio (alcalinização) pode diminuir a sensação de dor 12,13,[16][17][18][19] e a latência 9 . A lidocaína infiltrada no subcutâneo mostrou ter menores escores de dor quando o pH de sua solução aproxima-se do pH fisiológico.…”
Section: Discussionunclassified
“…Onset should be respected, or else there will be risk of triggering painful stimulation with no benefit for patients. Some studies have shown that mixing local anesthetic and sodium bicarbonate (alkalinization), may decrease painful sensation 12,13,[16][17][18][19] and onset 9 . Subcutaneous lidocaine infiltration has shown lower pain scores when its pH is close to physiological pH.…”
Section: Discussionmentioning
confidence: 99%
“…Também é interessante notar que essa teoria prevê a ligação inespecífica de grande quantidade de AL na fase lipídica, para que haja a alteração significante da fluidez e permeabilidade da membrana. 104 É a lipofilicidade dos AL que permite a concentração de grandes quantidades do composto nas membranas, o que facilitaria seu acesso aos sítios de ação na proteína-canal e determinaria a potência do bloqueio nervoso. 13 Sabe-se ainda que a interação específica dos AL com os canais de sódio é dependente do estado conformacional destes, ocorrendo preferencialmente quando do estado inativado, provocando desta forma a não condução de íons.…”
Section: Conclusõesunclassified